Belize : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
The authorities' economic policy seeks to sustain strong economic growth mainly through low taxes, large public investment, and the provision of credit to the private sector through the state-owned Development Finance Corporation (DFC). The authorities expect the resulting high rate of economic growth to generate sufficient fiscal resources to reduce the public sector deficit and service the rapidly accumulating external public debt. Executive Directors welcomed the authorities' intention to reduce excess liquidity to help secure the sustainability of the exchange rate.